Pengujian Sistem Jaringan Dokumentasi Dan Informasi Menggunakan Black Box Testing Dan White Box Testing - Muhammad Helmi Satria Fedianto; Firza Prima Aditiawan; Muhammad Muharrom Al Haromainy (Pusat Riset dan Inovasi Nasional, 2024)
Information systems in a company are important to increase productivity and quality in the company. With the development of technology today, it is certainly an convenience for companies in making information systems to support the performance of the company. To ensure the application runs according to functionality and find undiscovered errors in anticipation of upcoming errors, System testing is needed using Black Box and White Box to find errors in code structure and function errors in forms, interface design and data structures so that it can provide recommendations in accordance with the problems found and also facilitate program code maintenance or program code development in the future. From the test results, no problems were found in the login function and the majority of forms did not have handling to check empty input fields and obtained an effectiveness value of 62.5%..